2012
DOI: 10.1039/c2cc18163k
|View full text |Cite
|
Sign up to set email alerts
|

Helical phase from blending of chiral block copolymer and homopolymer

Abstract: The phase behavior of the binary blends of polystyrene-b-poly(L-lactide) chiral block copolymer (BCP*) and polystyrene homopolymer (HS) is found to be strongly dependent on the molecular weight (M(n)) of the HS. A helical phase is formed in the blends with low-M(n) HS due to an enhancement of helical steric hindrance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…[54] Given the relatively well-established understanding on the synthesis, physical properties, good degradability, and biocompatibility of PLLA/PDLA, there has been a litany of studies on the self-assembly of PLLA-/PDLA-based BCPs*. [35,38,[55][56][57][58] Besides, α-amino acids were also widely employed for the preparation of BCPs*. [37] For instance, PBLG-/PBDG-based BCPs* (PBLG: poly(γ-benzyl-L-glutamate), PBDG: poly(γ-benzyl-D-glutamate)) attracted a large number of studies.…”
Section: Molecular and Conformational Chirality Of Bcps*mentioning
confidence: 99%
See 2 more Smart Citations
“…[54] Given the relatively well-established understanding on the synthesis, physical properties, good degradability, and biocompatibility of PLLA/PDLA, there has been a litany of studies on the self-assembly of PLLA-/PDLA-based BCPs*. [35,38,[55][56][57][58] Besides, α-amino acids were also widely employed for the preparation of BCPs*. [37] For instance, PBLG-/PBDG-based BCPs* (PBLG: poly(γ-benzyl-L-glutamate), PBDG: poly(γ-benzyl-D-glutamate)) attracted a large number of studies.…”
Section: Molecular and Conformational Chirality Of Bcps*mentioning
confidence: 99%
“…Some of the key elements in this elucidation were extensively studied and manifested, that is, the intramolecular chiral interaction between PS and PLLA/PDLA, and the chiral steric hindrances. [55,57,80] The crystallization of PLLA/PDLA was demonstrated as another key factor to the self-assembly of PS-b-PLLA/PSb-PDLA BCPs* in bulk/films. By taking advantage of real time in situ SAXS and wide-angle X-ray diffraction, Grason and Russell et al indicated that the self-assembly of PS-b-PLLA/PS-b-PDLA entailed a sophisticated competition between incompatibility-driven microphase separation and the crystallization of PLLA/PDLA.…”
Section: Self-assembly Of Bcps* In Bulk or Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Nolte and co‐workers used charged chiral BCPs to generate hierarchical superstructures with helical sense8a and, more recently, Ho et al. reported the formation of different helical textures by the self‐assembly of poly(styrene)‐ b ‐poly( L ‐lactide) BCPs 8ei. In these works, the presence of chiral centres in the main chain of the BCPs has been postulated as the main factor to induce the formation of helical morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…In these works, the presence of chiral centres in the main chain of the BCPs has been postulated as the main factor to induce the formation of helical morphologies. Indeed, these chiral centres can induce helical conformations in one of the segments of the BCP, which can be transferred to a nanostructure (helical aggregate) during the self‐assembly in the so‐called “chirality effect” 8ei. New fundamental insight into the chirality effect on the self‐assembly of BCPs can be provided by means of systematic modification (i.e., tuning) of the helicity of one of the blocks (e.g., by controlling the number of chiral centres), without altering other parameters, such as molecular weight, block ratio, or solubility.…”
Section: Introductionmentioning
confidence: 99%